2011
DOI: 10.1074/jbc.m110.151647
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Proprotein Convertase SKI-1 Blocks Transcription of Key Extracellular Matrix Genes Regulating Osteoblastic Mineralization

Abstract: Mineralization, a characteristic phenotypic property of osteoblastic lineage cells, was blocked by 4-(2-aminoethyl) benzenesulfonyl fluoride hydrochloride (AEBSF) and decanoyl-Arg-Arg-Leu-Leu-chloromethyl ketone (dec-RRLLcmk), inhibitors of SKI-1 (site 1; subtilisin kexin like-1) protease. Because SKI-1 is required for activation of SREBP and CREB (cAMP-response element-binding protein)/ATF family transcription factors, we tested the effect of these inhibitors on gene expression. AEBSF decreased expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 64 publications
0
35
0
Order By: Relevance
“…Interestingly, MBTPS1 is required for the transcription of a number of bone matrix and mineralization-related genes including type XI collagen, Phex, Dmp1, fibronectin, and fibrillin in bone osteoblasts and osteocytes. Correspondingly, inactivation of MBTPS1 by AEBSF or specific inhibitor decanoyl-Arg-Arg-Leu-Leu-chloromethyl ketone blocks transcription of the aforementioned genes and inhibits mineralization (13,14). These results demonstrated that the differentiated phenotype of osteoblastic cells and possibly osteocytes depends upon MBTPS1.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…Interestingly, MBTPS1 is required for the transcription of a number of bone matrix and mineralization-related genes including type XI collagen, Phex, Dmp1, fibronectin, and fibrillin in bone osteoblasts and osteocytes. Correspondingly, inactivation of MBTPS1 by AEBSF or specific inhibitor decanoyl-Arg-Arg-Leu-Leu-chloromethyl ketone blocks transcription of the aforementioned genes and inhibits mineralization (13,14). These results demonstrated that the differentiated phenotype of osteoblastic cells and possibly osteocytes depends upon MBTPS1.…”
mentioning
confidence: 66%
“…Although microCT analyses revealed no differences in trabecular or cortical bone mineral density or morphological parameters between cKO and control tibiae, three-point bending studies on femora demonstrated a significant 25% gain in stiffness in Mbtps1-deficient bone (p ϭ 0.01). We rationalize this outcome in terms of a requirement for MBTPS1 for transcription of bone matrix genes including fibronectin, fibrillin2, and collagen XI (13). Because expression was not down-regulated in osteocyte-enriched bone (array data deposited at NCBI under accession number GSE69975), MBTPS1 regulation of these mineralization-related genes may be restricted to osteoblast-like cells (13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations